Exploring Social Media Marketing (SMM) in Shaping Purchase Intentions: The Mediating Role of Brand Awareness, Brand Image, and Brand Trust in the Beauty Industry Among Gen Z and Y - Mukti, Vina Apriliani (BIMA Journal (Business, Management, & Accounting Journal), 2024)
Purpose: To explore the influence of Social Media Marketing (SMM) on consumer Purchase Intention in the Indonesian beauty industry, with the mediation role of Brand Awareness, Brand Image, and Brand Trust. Method:  A quantitative approach with purposive sampling on 270 active users of TikTok and Instagram in Tasikmalaya, especially Generation Z and Y. Data was analyzed using SEM with AMOS 26. Results: The results of the study show that Social Media Marketing has a significant effect on Brand Awareness, Brand Image, and Brand Trust. However, only Brand Image and Brand Trust have a direct influence on Purchase Intention, while Brand Awareness and Social Media Marketing do not have a direct effect on Purchase Intention.  Findings: Purchasing Intentions are influenced more by Brand Image and Brand Trust than by Brand Awareness.  Novelty: This study highlights the important role of Brand Image and Brand Trust in influencing Purchase Intention through Social Media Marketing in the Indonesian beauty industry. Originality: This research fills in the gaps in marketing literature by focusing on the interaction between Brand Awareness, Brand Image, and Brand Trust in shaping purchasing Intentions through Social Media Marketing in the Indonesian beauty industry. Conclusions: To increase Purchase Intention through Social Media Marketing (SMM), beauty brands in Indonesia need to focus their efforts on strengthening Brand Image and Brand Trust, while Brand Awareness plays a role as the first step in building relationships with consumers. Type Of Paper : Empirical Research Paper